Oral hygiene in patients with prosthetic replacements: Oral prosthetics and hygiene - Stojkovic, Natasa (Education and Research in Health Sciences, 2024)
The plaque and debris control are necessary to prevent inflammatory periodontium disease and dental caries, since plaque is considered as the major etiological factor in phylogenesis of both diseases. Elimination of the plaque using toothbrush is commonly used method in oral hygiene. The electric brushes have been used since 1960s and they are currently had widely used in the high-income countries. Working sides of the brush are designed to clean all surfaces in the oral cavity including those retentive ones, and recently the design of manual and electric brushes has been focused to reach proximal surfaces of teeth. Patients’ technique of brushing the teeth, including force, duration, motivation, and movement, is also important for oral hygiene effectiveness. Dental floss and toothpaste have important role as secondary tools in oral prophylaxis. All mentioned appliances used for oral hygiene can be utilized for various kind of prosthetic replacements. However, different protocols were proposed for different prosthetic replacements. This paper considered all of these topics.
Keywords: toothbrushing; oral prophylaxis; dental plaque; toothbrushes